Single nucleotide polymorphisms in long noncoding RNA, ANRIL, are not associated with severe periodontitis but with adverse cardiovascular events among patients with cardiovascular disease. (6th May 2018) - Schulz, S.; Seitter, L.; Werdan, K.; Hofmann, B.; Schaller, H.‐G.; Schlitt, A.; Reichert, S.
Abstract : Background and Objective: Biological plausibility of an association between severe periodontitis and cardiovascular disease (CVD) has been proven. Genetic characteristics play an important role in both complex inflammatory diseases. Polymorphisms (single nucleotide polymorphisms [SNPs]) in the long noncoding RNA, antisense noncoding RNA in the INK4 locus (ANRIL), were shown to play a leading role in both diseases. The primary objectives of the study were to assess, among cardiovascular (CV angiographically proven ≥50% stenosis of a main coronary artery) patients, the impact of ANRIL SNPs rs133049 and rs3217992 on the severity of periodontitis and the previous history of coronary events, as well as on the occurrence of further adverse CV events. Material and Methods: The prevalence of severe periodontitis was analyzed in 1002 CV patients. ANRIL SNPs rs133049 and rs3217992 were genotyped. The prognostic value of both ANRIL SNPs for combined CV endpoint (stroke/transient ischemic attack [TIA], myocardial infarction, death from a CV‐related event, death from stroke) was evaluated after a 3‐year follow‐up period. Hazard ratios (HRs) were adjusted for established CV risk factors applying Cox regression. Results: ANRIL SNPs rs133049 and rs3217992 were not associated with severe periodontitis or history of CVD in CV patients. In the Kaplan‐Meier survival curve including the log rank‐test ( P = .036) and Cox regression (hazard ratio = 1.684, P = .009) the AA genotype of rs3217992 was shown to be an independent predictor for adverse CV events after 3 years of follow‐up. Conclusion: SNPs in ANRIL are not risk modulators for severe periodontitis and history of CVD in CV patients. The AA genotype of ANRIL SNPs rs3217992 possesses prognostic power for further CV events within 3 years of follow‐up.